Factors that affect the quality of Kikuyu grass (Cenchrus clandestinus) silage - Avellaneda-Avellaneda, Yesid (2023)
Introduction. The availability of Kikuyu grass silage helps reduce the seasonality of dairy production, but it is necessary to evaluate the factors affecting the ensiling process to maintain a quality similar to that of fresh forage. Objective. To evaluate the effect of regrowth age, chop size, wilting time with the use of additives on the quality of Kikuyu grass silage. Materials and methods. The study was conducted in Mosquera, Colombia, during 2020. The effect of regrowth age (28, 42, and 70 days), chop size (1.5 cm, 3.0 cm and whole plant), wilting time (0 and 6 hours), and the use of additives (crude glycerin and lactic acid bacteria (LAB)) on parameters such as chemical composition, in situ dry matter digestibility (ISDMD), pH dynamics, volatile fatty acid (VFA) profile, dry matter losses, and organoleptic quality was evaluated. The data was analyzed using a completely randomized design with a factorial arrangement. Results. The use of 70-day regrowth Kikuyu grass reduced (p<0.05) crude protein, digestibility, and energy, while increasing cell wall content and dry matter (DM) of the silage. Additive use reduced (p<0.05) the final pH of mature grass. Small chop size or inclusion of crude glycerin in the whole plant increased (p<0.05) ISDMD. Additive use reduced (p<0.05) the final pH of silage made with the whole plant. Pre-ensiling wilting increased (p<0.05) the DM and final pH, but reduced (p<0.05) crude protein and lactic acid. Conclusion. The use of tender forage, small chop size, and fresh bagging improved the quality of Kikuyu grass silage. The use of mature forage requires the application of additives.